Peranan Alat Bukti Elektronik dalam Tindak Pidana Pencemaran Nama Baik - I Putu Angga Permana; I Made Arjaya; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
This study is included in the category of empirical legal research carried out to fulfill the following objectives, 1) Assessing the rules related to criminal act of defamation in the Information and Electronic Transactions Law, 2) Examining the process of legal proof in criminal act of defamation under the Law of Information and Electronic Transactions. From the results of data analysis, it can be concluded that along with the increasing number of criminal cases through online media, the enforcement of electronic documents as legal evidence becomes very important due to the absence of physical evidence. The rules regarding the criminal act of defamation are included in the